Spinal Anaesthesia: Is it Safe in Younger Children? (Journal of Armed Forces Medical College, Bangladesh, 2010)
The characteristics of spinal block including ease of performance, efficacy, adverse effects and complicationswere evaluated in 78 children aged between 2-6 years undergoing different types of surgery in lower part ofbody. Spinal block was performed in sedated children with 0.5% hyperbaric bupivacaine at a dose of 0.25mg/kg. Haemodynamically patients were stable in most of the cases. In general pulse rate was increased by9.8% while systolic and diastolic blood pressures were reduced by 6.8% and 8.7% respectively from baselinelevel after 15 min of block, which didn't warrant any active management. One patient was treated withinjection atropine for bradycardia (20% from baseline level) and were easily managed with injectionephedrine hydrochloride. Two patients had insignificant sinus arrhythmia during operation and threerequired temporary supplemental oxygen support by mask to maintain oxygen salutation >94%. Motor blockwas complete in all but two cases. Sensory block showed wide variation of height, from first thoracic toseventh thoracic (4th thoracic). Time of two segment regression of block was 74 min (range 30-190 min). Meantime of giving rescue analgesic after spinal block was 118 min (range 59-240 min). One patient vomited andfive had shivering in the recovery room. There was no incidence of systemic toxicity of bupivacaine (urinaryretention, post dural puncture headache or any other neurological complication). Spinal block was observed tobe easier, safer and very effective anaesthetic technique even in younger children.Key words: Spinal anaesthesia; children; complication.DOI: 10.3329/jafmc.v6i1.5988Journal of Armed Forces Medical College, Bangladesh Vol.6(1) 2010 p.25-28